2009
DOI: 10.1007/s11250-009-9503-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Oestrus ovis infection of sheep in northeast Spain (mid-Ebro Valley)

Abstract: Slaughterhouse surveys to determine the prevalence and intensity of larval Oestrus ovis Linnaeus (Diptera: Oestridae) in sheep, were conducted monthly for 1 year in northeastern Spain. The prevalence of O. ovis in 120 sheep in northeast Spain was 84.2%. The monthly prevalence ranged from 62.5% in January to 100% in June and October. Of the 3,831 larvae collected, 3,005 were first instar larvae (78.4%), 744 second instar larvae (19.4%), and 82 third instar larvae (2.1%). The mean larval burden per infected shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
4
15
1
2
Order By: Relevance
“…The mean intensity of infestation reported in this study (16.8) was similar to that previously reported in Sardinia, Italy (SCALA et al, 2001) and Southwestern Spain (ALCAIDE et al, 2003), with mean intensities of 19 and 18.5 larvae per infested head, respectively; but lower than that found in Southwestern France with 24.8 larvae (YILMA;DORCHIES, 1991) and Northeastern Spain with 37.9 (GRACIA et al, 2010). It is noteworthy that a high percentage of first larval instar were found by those authors, especially during the colder months.…”
Section: Discussionsupporting
confidence: 89%
“…The mean intensity of infestation reported in this study (16.8) was similar to that previously reported in Sardinia, Italy (SCALA et al, 2001) and Southwestern Spain (ALCAIDE et al, 2003), with mean intensities of 19 and 18.5 larvae per infested head, respectively; but lower than that found in Southwestern France with 24.8 larvae (YILMA;DORCHIES, 1991) and Northeastern Spain with 37.9 (GRACIA et al, 2010). It is noteworthy that a high percentage of first larval instar were found by those authors, especially during the colder months.…”
Section: Discussionsupporting
confidence: 89%
“…When compared with the studies from the world, while it was higher than in Libya (51.66%) (Negm-Eldin et al, 2015), Greece (48.6%) (Papadopoulos et al, 2006), Saudi Arabia (53.5%) (Hanan, 2013) and Brazil (13.7%) (Silva et al, 2013), it was lower than in Central Oramina Ethipia (94.6%) (Alem et al, 2010) and Italy (91%) (Scala et al, 2001). The ratios are similar with those from Spain (71.1% and 75.9%) (Alcaide et al, 2003;Gracia et al, 2010), Morocco and Greece (69.2% and 75.9%) (Pandey and Ouhelli, 1984;Papadopoulos et al, 2010). No studies have been encountered investigating the prevalence of oestrosis in goats.…”
Section: Resultssupporting
confidence: 50%
“…In Saudi Arabia, Hanan (2013) found 53.5% which is lower compared to data from Spain, which described a range of prevalence between 71.1% and 82.4% (Alcaide et al 2003, Gracia et al 2010. Research done in Morocco and Greece found similar prevalence rates (69.2% and 75.9%), although the weather in these countries are different (Pandey & Ouhelli 1984, Papadopolus et al 2010).…”
Section: Discussionmentioning
confidence: 92%